LEGAL FRAMEWORK AND STATE POLICY IN THE DEVELOPMENT OF PRIVATE ENTREPRENEURSHIP IN UZBEKISTAN - Xolbekov Abdujamol Yaxshiboyevich (Bright Mind Publishing, 2025)
This article explores the legal framework and state policy in the development of private entrepreneurship in Uzbekistan. The article outlines the categorization of enterprises, measures to protect entrepreneurs from excessive inspections, and legal guarantees for property rights and investment protection. The article concludes by emphasizing Uzbekistan’s improved global business ranking and the positive outlook for private entrepreneurship development.
Keywords: Uzbekistan, private entrepreneurship, legal framework, state policy, Entrepreneurship Code, small business, business reforms, investment protection, tax incentives, digital economy, business regulation.